ACTINIC CHEILITIS: CO2 LASER ABLATION VERSUS VERMILIONECTOMY – ELEVEN YEAR ANALYSIS - Cabral, Rita; Teixeira, Vera; Vieira, Ricardo; Figueiredo, Américo (Journal of the Portuguese Society of Dermatology and Venereology, 2014)
Background: Actinic cheilitis is a pre-malignant lesion affecting predominantly the vermilion of the inferior lip of male patients. Objectives: Our aim was compare two treatment options for Actinic cheilitis: ablation with CO2 laser and vermilionectomy. Methods: Retrospective study of patients with Actinic cheilitis treated with CO2 laser ablation or vermilionectomy, in an 11 year period. Results: 51 caucasian patients were included, 43 (84%) of which were submitted to CO2 laser ablation and the 8 (16%) remainder to vermilionectomy. Mean follow-up time was 30,8 months (3 to 84 months). No recurrences were found in the patients submitted to vermilionectomy and in 72,5% of the patients treated with CO2 laser ablation, with no statistical significance (p>0,05). There was evolution to squamous cell carcinoma in one patient treated by CO2 laser ablation, after 50 months (surgically removed, no recurrence to date). Conclusion: Despite this reduced series, our results are similar to those available in the literature, concerning the recurrence rate after laser CO2 ablation.